Efektifitas berbagai sumber air sebagai pelarut terhadap kualitas pupuk organik cair (POC) dari limbah RPH - Maria Erviana Kusuma; K Kastalani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
This study aims to determine the effect of various water sources on the quality of liquid organic fertilizer from RPH waste and to determine which water sources have the best effect on the quality of liquid organic fertilizer from RPH waste. This research was conducted at the practical location of the Faculty of Animal Science, Palangka Raya Christian University. This study was designed using a completely randomized design with a single treatment of various types of water in the manufacture of liquid organic fertilizer with 3 replications, namely A = 5 liter river water + 2 kg cow manure + 400 gr rumen + 160 gr brown sugar. + EM4 40 cc, B = 5 liter rain water + 2 kg cow manure + 400 g rumen + 160 g brown sugar + EM4 40 cc, C = 5 liters peat water + 2 kg cow manure + 400 rumen gr + brown sugar 160 gr + EM4 40 cc and D = well / drill water 5 liters + 2 kg cow manure + rumen 400 gr + brown sugar 160 gr + EM4 40 cc. The results of this study were that the provision of various water sources did not affect the quality of liquid organic fertilizer from RPH waste. Keywords : Water sources, quality, liquid organic fertilizer.